2018
DOI: 10.3390/min8020075
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transition of Inorganic Silica–Carbonate Composites Towards Curved Lifelike Morphologies

Abstract: The self-assembly of alkaline earth carbonates in the presence of silica at high pH leads to a unique class of composite materials displaying a broad variety of self-assembled superstructures with complex morphologies. A detailed understanding of the formation process of these purely inorganic architectures is crucial for their implications in the context of primitive life detection as well as for their use in the synthesis of advanced biomimetic materials. Recently, great efforts have been made to gain insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…37 The morphology, observed through SEM, of the silica-strontium carbonates formed at 50 °C revealed that the control sample depicts structures of leaves and flowers (Figure 7B), which is the typical structure reported by other authors for these compounds. 38,39 The silica-strontium carbonates synthesized with gDNA showed a spherical morphology, formed by crystals in the form of perfectly ordered needles (Figure 7B). The samples obtained in the presence of pDNA formed structures of hollow stems with crystals perfectly ordered in their ends (Figure 7B).…”
Section: Crystal Growth and Designmentioning
confidence: 99%
“…37 The morphology, observed through SEM, of the silica-strontium carbonates formed at 50 °C revealed that the control sample depicts structures of leaves and flowers (Figure 7B), which is the typical structure reported by other authors for these compounds. 38,39 The silica-strontium carbonates synthesized with gDNA showed a spherical morphology, formed by crystals in the form of perfectly ordered needles (Figure 7B). The samples obtained in the presence of pDNA formed structures of hollow stems with crystals perfectly ordered in their ends (Figure 7B).…”
Section: Crystal Growth and Designmentioning
confidence: 99%
“…In the past fifty years, several techniques have been developed for the synthesis and characterization of these biomorphs [8]. Several studies published elsewhere have evaluated the impact of physical parameters including temperature [8], electric fields [9], UV light [10], pH, CO 2 content and growth in solution or gels on the formation of biomorphs [11][12][13][14]. In addition, the influence of cationic additives [15] and biomolecules such as nucleic acids and amino acids in the synthesis of these biomorphs has also been recently reviewed [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Under some conditions, more atypical morphologiessuch as flower-like forms, 'trumpets', 'corals', 'moths', 'snails' or 'mushrooms' (Fig. 2h)can also be found (Opel et al 2018;Rouillard et al 2018).…”
Section: Carbonate-silica Biomorphsmentioning
confidence: 99%